Effect of microencapsulation with Maillard reaction products of whey proteins and isomaltooligosaccharide on the survival of Lactobacillus rhamnosus. (November 2016) - Liu, Lu; Li, Xiaodong; Zhu, Yongming; Massounga Bora, Awa Fanny; Zhao, Yongbo; Du, Lingling; Li, Donghua; Bi, Weiwei
Abstract: Lactobacillus rhamnosus ( L. rhamnosus ) was microencapsulated with Maillard reaction products of whey protein and isomaltooligosaccharide (WIMRPs) through cold gelation within emulsification system and its survival was evaluated after exposure to simulated gastrointestinal conditions. The Maillard reaction of whey protein and isomaltooligosaccharide (4:1) occurred in wet heating conditions (90 °C, 4 h) forming high molecular weight conjugate. The WIMRPs microspheres showed the highest encapsulation yield (88.88%) after cold gelation within emulsification system compared with the microcapsules produced with the mixture of whey protein and isomaltooligosaccharide (WIMIX). The shape of WIMRPs microparticles was more spherical and smooth. The microparticles WIMRPs and WIMIX had mean diameter of 183 μm and 201 μm, respectively. WIMRPs provided better protection of probiotics after exposure of the microparticles to simulated gastrointestinal conditions, with the count of 7.48 and 7.17 log10  cfu/g respectively after 90 min incubation in Simulated Gastric Fluid (SGF) and 3% bile salt solution. The microspheres could be completely released in 60 min. Highlights: The whey protein and isomaltooligosaccharide (4:1) formed high molecular weight conjugate at 90 °C for 4 h. The microspheres' shape is more spherical than the WIMIX, around 89% encapsulation yield was achieved. The WIMRPs provided better protection of probiotics after exposure to simulated gastrointestinal conditions. The encapsulated Lactobacillus rhamnosus could be released from microspheres in 60 min (9.13 log CFU/g).